The Relationship between Knowledge and Attitudes towards the Actions of Bakso Snack Traders at Schools in Kabanjahe, Karo Regency in 2022 - Susanti Br Perangin-Angin; Selvina Br Sembiring (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
Meatballs are food that is easily contaminated. This study aims to determine the relationship between knowledge and attitudes towards the actions of meatball snack traders at schools in Kabanjahe, Karo Regency in 2022. This type of research is an analytic survey with a cross sectional approach. The population is meatball traders totaling 31 people and a sample of 31 people with a total sampling technique. The results of the study are knowledge p = 1,000 (p = 0.05) meaning that there is no relationship between knowledge and the actions of meatball snack traders at school. Meatball snack traders at schools in Kabanjahe. Advice on personal hygiene and equipment for traders